2007
DOI: 10.1016/j.biocel.2007.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Transdetermination: Drosophila imaginal disc cells exhibit stem cell-like potency

Abstract: Drosophila imaginal discs, the primordia of the adult fly appendages, are an excellent system for studying developmental plasticity. Cells in the imaginal discs are determined for their disc-specific fate (wingness, legness) during embryogenesis. Disc cells maintain their determination during larval development, a time of extensive growth and proliferation. Only when prompted to regenerate do disc cells exhibit lability in their determined identity. Regeneration in the disc is mediated by a localized region of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 112 publications
(124 reference statements)
2
46
0
Order By: Relevance
“…This result suggested that compensatory proliferation of imaginal disc tissue was taking place, in which the remaining living tissue could rescue the appropriate size of the disc. This ability of imaginal discs to regenerate after injury has been confirmed by other researches either in vivo and in vitro (Marsh and Theisen, 1999;McClure and Schubiger, 2007). Subsequent studies support the activation of this compensatory proliferation activity after apoptosis or injury triggering either tissue repair or normal growth processes and regulating organ size during development (Wells et al, 2006;Fan and Bergmann, 2008;Pérez-Garijo et al, 2009).…”
Section: Injury and Regeneration Of Drosophila Imaginal Discs: A Modementioning
confidence: 56%
See 1 more Smart Citation
“…This result suggested that compensatory proliferation of imaginal disc tissue was taking place, in which the remaining living tissue could rescue the appropriate size of the disc. This ability of imaginal discs to regenerate after injury has been confirmed by other researches either in vivo and in vitro (Marsh and Theisen, 1999;McClure and Schubiger, 2007). Subsequent studies support the activation of this compensatory proliferation activity after apoptosis or injury triggering either tissue repair or normal growth processes and regulating organ size during development (Wells et al, 2006;Fan and Bergmann, 2008;Pérez-Garijo et al, 2009).…”
Section: Injury and Regeneration Of Drosophila Imaginal Discs: A Modementioning
confidence: 56%
“…5A). This phenomenon, which is characterized by the change of cell identity by a reprogrammable mechanism, is known as transdetermination McClure and Schubiger, 2007;McClure et al, 2008). Transdetermination has been ascribed to the action of ectopic morphogens, which induce cells to activate incorrect signaling cascades Schubiger, 1998, 2003), chromatin modifications by PcG proteins or other factors (Lee et al, 2005;Klebes et al, 2005).…”
Section: Injury and Regeneration Of Drosophila Imaginal Discs: A Modementioning
confidence: 99%
“…(b) ''Transdetermination,'' in which a committed, but not yet fully differentiated, cell type or a progenitor cell is directly converted into another cell type without going back to or through a pluripotent stage. For example, alterations of imaginal disc cell fate can be seen in Drosophila melanogaster in the regenerating disc (e.g., a wing instead of a leg) [16]. (c) In ''serial heteromorphosis,'' similarly developed body parts or tissues, such as segments or appendages, develop in the wrong place during embryogenesis or regeneration in both Crustacea and insects.…”
Section: Figure 1 Types Of Lineage Reprogramming and Definition Of Imentioning
confidence: 99%
“…It was found that specific genes were expressed at higher levels in the teratomas formed by iPS cells than in those formed by ES cells, and two of these genes, zymogen granule protein 16 and HORMA domain-containing 1, were specifically targeted in immune attacks. Epigenetic differences between iPS and ES cells and/or mutations in the coding sequences of iPS cells could result in the ectopic expression of these minor antigens and the immunogenicity of iPS cell derivatives [67,[83][84][85][86][87].…”
Section: Immunogenicity Of Transdifferentiated Cellsmentioning
confidence: 99%
“…The classic and elegant transplantation experiments showing imaginal disc regeneration are one example. 12,13 They have recently published a paper on a genetic approach to find candidates specifically required in the regeneration process. 14 The screen reported at this meeting, concentrated on the genes that are activated in response to Wg upon the formation of a regeneration blastema.…”
Section: Regenerationmentioning
confidence: 99%